Hypothetical In-vivo Behavior of Pediatric Dosage Forms: Ibuprofen Oral Suspensions: Hypothetical in-vivo behavior of ibuprofen suspensions - Reyes-Castillo, Stephanie Marlen; Reyes-Ramirez, Felipe Dino; Cedillo-Diaz, Luis Antonio; Contreras-Jimenez, Juan Manuel; Medina-López, José Raúl (Iranian Journal of Pharmaceutical Sciences, 2025)
The hypothetical plasma concentration-time profiles of ibuprofen pediatric formulations using in-vitro release data of the mini-paddle apparatus and the USP apparatus were proposed. Dissolution conditions were as follows: a mini-paddle apparatus at 75 rpm, 200 mL of medium, a USP apparatus 4 laminar flow at 16 mL/min, and phosphate buffer (pH 6.8). Five commercial formulations (reference and four multi-source drug products) were used. Samples were taken at previously established times for up to 60 minutes. The dissolved drug was quantified by UV derivative spectrophotometric analysis. Profiles were compared with different approaches, and dissolution data were fitted with several mathematical equations. Predicted in vivo behavior was calculated using dissolution data from both apparatuses and published pharmacokinetic information through a convolution approach. Validation of the results was carried out by calculating the prediction error (PE) for the hypothetical peak plasma level (Cmax) as well as the area under the curve from zero to infinity (AUC0-inf). Calculations are valid if PE is equal to or less than 10%. Considering the f2 value, similar in-vitro release curves of all suspensions were found using data from the USP apparatus 4 (f2 > 50). No statistically significant differences were calculated for the release parameters of B and C drug products, respectively, using data from the USP apparatus 4. PE < 10% for Cmax and AUC0-inf in the same formulation was only found with R, B, and C drug products, based on data from the USP apparatus 4. This apparatus appears to be the appropriate choice for assessing the biopharmaceutical quality of pediatric ibuprofen formulations.